CCTO ceramic

CaCu3Ti4-xNbxO12 ceramics were prepared by sol-gel method, which solved the problems of high sintering temperature and insufficient dielectric performance of existing CCTO ceramics, and achieved low energy consumption, high dielectric constant and low dielectric loss ceramic materials.

CN119613106APending Publication Date: 2025-03-14QUANZHOU NORMAL UNIV

Patent Information

Application Number
CN202411943250.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The sintering temperature of existing copper calcium titanate (CCTO) ceramic materials is high, resulting in increased energy consumption and doping of La and Co elements is required to increase the dielectric constant and reduce dielectric loss.

Method used

CaCu3Ti4-xNbxO12 ceramics were prepared by sol-gel method. Ceramic samples with low dielectric loss and high dielectric constant were achieved by adjusting the Nb doping concentration, solution pH value and drying gel temperature.

Benefits of technology

At a lower sintering temperature, CaCu3Ti4-xNbxO12 ceramics with high dielectric constant and low dielectric loss were prepared, which improved the density and mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613106A_ABST
    Figure CN119613106A_ABST
Patent Text Reader

Abstract

The invention discloses a CCTO dielectric ceramic, and belongs to the technical field of dielectric ceramic synthesis. Calcium nitrate tetrahydrate, copper nitrate trihydrate, tetrabutyl titanate and niobium oxalate hydrate are used as raw materials, a precursor solution is prepared according to the molar ratio of calcium to copper to titanium to niobium being 1: 3: 4-x: x, the PH is adjusted, colloid obtained after aging is dried and ground, then high-temperature sintering is conducted in a muffle furnace, tabletting is conducted after the colloid is mixed with an adhesive, annealing is conducted, and finally the high-density, good-uniformity and high-temperature-resistant titanium-titanium alloy is obtained. And the single-doped CaCu3Ti (4-x) NbxO12 ceramic sample has the advantages of low dielectric loss and high dielectric constant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of dielectric ceramic synthesis, and in particular to a CCTO dielectric ceramic. Background Art

[0002] Calcium copper titanate (CCTO) is a high dielectric constant material, which is widely used in capacitors, energy storage devices and other electronic components. Patent CN 109776089 A discloses a calcium copper titanate-based ceramic material and a preparation method thereof. The low-frequency dielectric loss of the material is significantly reduced by co-doping with La and Co while maintaining a high dielectric constant, overcoming the disadvantage of the traditional method of reducing the dielectric constant by doping high-insulation ceramics. However, its optimal sintering temperature is 1100°C. A higher sintering temperature will lead to an increase in energy consumption. At the same time, La and Co need to be doped to increase the dielectric constant and reduce the dielectric loss. Therefore, the present application provides a single metal doped CaCu3Ti with a low sintering temperature, a high dielectric constant and low dielectric loss. 4-x Nb x O 12 ceramics. Summary of the invention

[0003] The purpose of this application is to provide a CCTO dielectric ceramic to solve the technical problem in patent CN 109776089 A that the sintering temperature is high, resulting in increased energy consumption.

[0004] The present application provides a CCTO dielectric ceramic, the chemical formula of which is CaCu3Ti 4-x Nb x O 12, Wherein, x>0, the preparation method of CCTO ceramic material is as follows: S1, calcium nitrate tetrahydrate and deionized water were mixed and stirred to prepare solution A; copper nitrate trihydrate and anhydrous ethanol were mixed and stirred to prepare solution B; tetrabutyl titanate solution and anhydrous ethanol were mixed to prepare solution C, and C 10 H5B 20 xH2O and deionized water were mixed and stirred to prepare solution D; S2, mixing solution A, solution B, solution C and solution D to obtain a precursor solution; S3, adding 65% concentrated nitric acid to the precursor solution obtained in S2, adjusting the pH to 2-3, covering with plastic wrap, and after magnetic stirring, aging the obtained CCTO precursor solution at room temperature to obtain CCTO colloid; S4, placing the CCTO colloid obtained in S3 in a vacuum oven at 80°C to dry to obtain a dry gel, and then grinding it into powder in a ball mill; S5: The ball-milled powder in S4 is placed in a corundum crucible washed with anhydrous ethanol and dried, and sintered in a muffle furnace to obtain powder E.

[0005] S6. Mix the powder E obtained in S5 with a 5% PVA adhesive, and press the mixture into tablets using a tablet press to obtain round tablets with smooth surfaces.

[0006] S7, annealing the wafer obtained in S6 in a muffle furnace to finally obtain CaCu3Ti 4-x Nb x O 12 Ceramic samples.

[0007] Preferably, in S1, the specific steps of mixing calcium nitrate tetrahydrate with deionized water to prepare solution A are: dissolving calcium nitrate tetrahydrate with deionized water as solvent, covering with plastic wrap and stirring on a magnetic stirrer for 20 minutes to obtain solution A.

[0008] Preferably, in S1, the specific steps of mixing copper nitrate trihydrate and anhydrous ethanol to prepare solution B are: adding copper nitrate trihydrate to anhydrous ethanol, covering with plastic wrap and stirring on a magnetic stirrer for 40 minutes to obtain solution B.

[0009] Preferably, in S1, the specific steps of mixing tetrabutyl titanate and anhydrous ethanol to prepare solution C are: after adding tetrabutyl titanate to anhydrous ethanol, cover with plastic wrap and stir on a magnetic stirrer for 20 minutes to obtain solution C.

[0010] Preferably, in S1, C 10 H5B 20 The specific steps of mixing xH2O and deionized water to prepare solution D are: 10 H5B 20 After adding deionized water, xH2O was added, the mixture was covered with plastic wrap and stirred on a magnetic stirrer for 40 min to obtain solution D.

[0011] Preferably, in S5, the powder after ball milling in S4 is placed in a corundum crucible washed with anhydrous ethanol and dried, and sintered in a muffle furnace to obtain powder E. The specific steps are: placing the powder after ball milling in S4 in a corundum crucible washed with anhydrous ethanol and dried, sintering, heating from room temperature to 350°C at a heating rate of 5°C / min, keeping the temperature for 3 hours, then heating to 900°C, keeping the temperature for 10 hours, and cooling to room temperature to obtain powder E.

[0012] Preferably, in S7, the wafer obtained in S6 is annealed in a muffle furnace to finally obtain CaCu3Ti 4-x Nb x O 12The specific steps of the ceramic sample are as follows: the muffle furnace program is set to 300℃ for 1 hour, then heated to 700℃ for 1 hour, then heated to 1000℃ for 6 hours for annealing, and the muffle furnace is cooled to room temperature to finally obtain CaCu3Ti 4-x Nb x O 12 Ceramic samples.

[0013] Therefore, the present application provides a CCTO ceramic having the following beneficial effects: 1. Sol-gel method in the preparation of CaCu3Ti 4-x Nb x O 12 When making ceramics, the precursor solution is combined, dried to form a gel, and then calcined and dried to obtain nanoparticles. The nanoparticles have good crystallinity, strong component uniformity, and high phase purity. It is easy to prepare uniform mixed oxide ceramics. The obtained ceramics have increased density, are not easy to decompose, and have enhanced mechanical properties.

[0014] 2. The present invention uses a sol-gel method to prepare CCTO doped Nb ceramic powder, and through the control of the Nb doping concentration ratio, solution pH value, drying and gelling temperature and other intermediate processes, a CaCu3Ti with high density, good uniformity, low dielectric loss and high dielectric constant is achieved. 4-x Nb x O 12 (CCTNO) ceramic samples. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The XRD diagram of the ceramic sample obtained in Example 1-4 with an annealing temperature of 900°C; Figure 2 This is a SEM image of the ceramic sample obtained in Example 1-4 with an annealing temperature of 900°C; Figure 3 The dielectric constant of the ceramic samples of Examples 1-4 varies with frequency; Figure 4 is a graph showing the variation of the doping amount of the ceramic samples of Examples 1-4 with temperature; Figure 5 The dielectric loss of the ceramic samples of Examples 1-4 varies with frequency; Figure 6 The dielectric loss of the ceramic samples of Examples 1-4 varies with temperature; Figure 7 is a graph showing changes in leakage current of the ceramic samples of Examples 1-4; Figure 8 Graph showing the change in capacitance density of the ceramic samples of Examples 1-4 with temperature. DETAILED DESCRIPTION

[0016] The technical solution of the present invention is further illustrated by the following examples.

[0017] Example 1 (1) Using deionized water as solvent, calcium nitrate tetrahydrate was fully dissolved, and the mixture was covered with plastic wrap and stirred on a magnetic stirrer for 20 minutes to obtain a colorless and transparent solution A; (2) Take copper nitrate trihydrate and add anhydrous ethanol, cover with plastic wrap and stir on a magnetic stirrer for 40 minutes to obtain a blue transparent solution B. (3) Add tetrabutyl titanate solution to anhydrous ethanol, cover with plastic wrap, and stir in a magnetic stirrer for 20 minutes to form a colorless or light yellow solution C; (4) Using deionized water as solvent, C 10 H5B 20 After fully dissolving, cover with plastic wrap and stir on a magnetic stirrer for 40 minutes to obtain a colorless and transparent solution D; (5) Pour solution A into the continuously stirred solution C, wash beaker A three times with glacial acetic acid, and pour all the washing solution into beaker C. Then carefully and slowly pour solution B into the mixture of A + C. Similarly, wash it three times with glacial acetic acid and pour it into the mixture of A + C to obtain a mixed solution of A + B + C solutions. Then add solution D to the mixed solution of A + B + C. Wash the beaker of solution D three times with glacial acetic acid and pour it into the mixed solution of A + B + C to obtain a mixed solution of A + B + C + D.

[0018] (6) Add a small amount of 65% concentrated nitric acid to the mixed solution of A+B+C+D obtained in (5) to adjust the pH of the solution to 2-3, and cover with plastic wrap to prevent the solution from volatilizing. After magnetic stirring for 2 hours, a light blue CCTO precursor solution is obtained and aged at room temperature for 72 hours to obtain a light blue jelly-like CCTO colloid; (7) The light blue jelly-like CCTO colloid was placed in a vacuum oven at 80°C and dried for 96 hours to obtain a blue-green dry gel, which was then placed in a ball mill and ground into a blue-green powder.

[0019] (8) The blue-green powder after ball milling was placed in a corundum crucible that had been washed with anhydrous ethanol and dried, and sintered at high temperature in a muffle furnace from room temperature to 350°C at a heating rate of 5°C / min. After keeping the temperature for 3 hours, the temperature was increased to 900°C. After keeping the temperature for 10 hours, the powder was cooled to room temperature to obtain a brown powder sample.

[0020] (9) The powder sample obtained in (8) was uniformly mixed with a small amount of 5% PVA adhesive and tableted using a tablet press at a pressure of 10 MPa to obtain dark brown, smooth-surfaced discs.

[0021] (10) The muffle furnace program was set to keep the temperature at 300 °C for 1 hour, then to 700 °C for 1 hour, and then to 900 °C for 6 hours for annealing. The muffle furnace was cooled to room temperature, and finally CaCu3Ti with an annealing temperature of 900 °C was obtained. 3.95 Nb 0.05 O 12 Ceramic sample; the muffle furnace program was set to 300℃ for 1 hour, then to 700℃ for 1 hour, then to 1000℃ for 6 hours, and then annealed. The muffle furnace was cooled to room temperature, and finally the CaCu3Ti with an annealing temperature of 1000℃ was obtained. 3.95 Nb 0.05 O 12 Ceramic samples.

[0022] The surface of the prepared sample was ground and polished, the two electrodes of the ceramic piece were coated with conductive silver glue, and the electrical performance was tested after the wires were welded at both ends.

[0023] Example 2 (1) Using deionized water as solvent, calcium nitrate tetrahydrate was fully dissolved, and the mixture was covered with plastic wrap and stirred on a magnetic stirrer for 20 minutes to obtain a colorless and transparent solution A; (2) Take copper nitrate trihydrate and add anhydrous ethanol, cover with plastic wrap and stir on a magnetic stirrer for 40 minutes to obtain a blue transparent solution B. (3) Add tetrabutyl titanate solution to anhydrous ethanol, cover with plastic wrap, and stir in a magnetic stirrer for 20 minutes to form a colorless or light yellow solution C; (4) Using deionized water as solvent, C 10 H5B 20 After fully dissolving, cover with plastic wrap and stir on a magnetic stirrer for 40 minutes to obtain a colorless and transparent solution D; (5) Pour solution A into the continuously stirred solution C, wash beaker A three times with glacial acetic acid, and pour all the washing solution into beaker C. Then carefully and slowly pour solution B into the mixture of A + C. Similarly, wash it three times with glacial acetic acid and pour it into the mixture of A + C to obtain a mixed solution of A + B + C solutions. Then add solution D to the mixed solution of A + B + C. Wash the beaker of solution D three times with glacial acetic acid and pour it into the mixed solution of A + B + C to obtain a mixed solution of A + B + C + D.

[0024] (6) A small amount of 65% concentrated nitric acid was added to the mixed solution of A+B+C+D obtained in (5) to adjust the pH of the solution to 2-3, and the solution was covered with plastic wrap to prevent the solution from volatilizing. After magnetic stirring for 2 hours, a light blue CCTO precursor solution was obtained, which was aged at room temperature for 72 hours to obtain a light blue jelly-like CCTO colloid.

[0025] (7) The light blue jelly-like CCTO colloid was placed in a vacuum oven at 80°C and dried for 96 hours to obtain a blue-green dry gel, which was then placed in a ball mill and ground into a blue-green powder.

[0026] (8) The blue-green powder after ball milling was placed in a corundum crucible that had been washed with anhydrous ethanol and dried, and sintered at high temperature in a muffle furnace. The temperature was increased from room temperature to 350°C at a heating rate of 5°C / min and kept at that temperature for 3 hours. The temperature was then increased to 900°C and kept at that temperature for 10 hours. After cooling to room temperature, a brown powder sample was obtained.

[0027] (9) The powder sample obtained in (8) was uniformly mixed with a small amount of 5% PVA adhesive and tableted using a tablet press at a pressure of 10 MPa to obtain dark brown, smooth-surfaced discs.

[0028] (10) The muffle furnace program was set to keep the temperature at 300 °C for 1 hour, then to 700 °C for 1 hour, and then to 900 °C for 6 hours for annealing. The muffle furnace was cooled to room temperature, and finally CaCu3Ti with an annealing temperature of 900 °C was obtained. 3.9 Nb .1 O 12 Ceramic sample; the muffle furnace program was set to 300℃ for 1 hour, then heated to 700℃ for 1 hour, then heated to 1000℃ for 6 hours, annealed, and the muffle furnace was cooled to room temperature to finally obtain CaCu3Ti with an annealing temperature of 1000℃ 3.9 Nb 0.1 O 12 Ceramic samples.

[0029] The surface of the prepared sample was ground and polished, the two electrodes of the ceramic piece were coated with conductive silver glue, and the electrical performance was tested after the wires were welded at both ends.

[0030] Example 3 (1) Using deionized water as solvent, calcium nitrate tetrahydrate was fully dissolved, and the mixture was covered with plastic wrap and stirred on a magnetic stirrer for 20 minutes to obtain a colorless and transparent solution A; (2) Take copper nitrate trihydrate and add anhydrous ethanol, cover with plastic wrap and stir on a magnetic stirrer for 40 minutes to obtain a blue transparent solution B. (3) Add tetrabutyl titanate solution to anhydrous ethanol, cover with plastic wrap, and stir in a magnetic stirrer for 20 minutes to form a colorless or light yellow solution C; (4) Using deionized water as solvent, C 10 H5B 20 After fully dissolving, cover with plastic wrap and stir on a magnetic stirrer for 40 minutes to obtain a colorless and transparent solution D; (5) Pour solution A into the continuously stirred solution C, wash beaker A three times with glacial acetic acid, and pour all the washing solution into beaker C. Then carefully and slowly pour solution B into the mixture of A + C. Similarly, wash it three times with glacial acetic acid and pour it into the mixture of A + C to obtain a mixed solution of A + B + C solutions. Then add solution D to the mixed solution of A + B + C. Wash the beaker of solution D three times with glacial acetic acid and pour it into the mixed solution of A + B + C to obtain a mixed solution of A + B + C + D.

[0031] (6) Add a small amount of 65% concentrated nitric acid to the mixed solution of A+B+C+D obtained in (5) to adjust the pH of the solution to 2-3, and cover with plastic wrap to prevent the solution from volatilizing. After magnetic stirring for 2 hours, a light blue CCTO precursor solution is obtained and aged at room temperature for 72 hours to obtain a light blue jelly-like CCTO colloid; (7) The light blue jelly-like CCTO colloid was placed in a vacuum oven at 80°C and dried for 96 hours to obtain a blue-green dry gel, which was then placed in a ball mill and ground into a blue-green powder; (8) The blue-green powder after ball milling was placed in a corundum crucible that had been washed with anhydrous ethanol and dried, and sintered at high temperature in a muffle furnace from room temperature to 350°C at a heating rate of 5°C / min. After keeping the temperature for 3 hours, the temperature was increased to 900°C. After keeping the temperature for 10 hours, the powder was cooled to room temperature to obtain a brown powder sample.

[0032] (9) The powder sample of (8) was uniformly mixed with a small amount of 5% PVA adhesive and tableted using a tablet press at a pressure of 10 MPa to obtain dark brown, smooth-surfaced discs.

[0033] (10) The muffle furnace program was set to keep the temperature at 300 °C for 1 hour, then to 700 °C for 1 hour, and then to 900 °C for 6 hours for annealing. The muffle furnace was cooled to room temperature, and finally CaCu3Ti with an annealing temperature of 900 °C was obtained. 3.95 Nb 0.15 O 12 Ceramic sample; the muffle furnace program was set to 300℃ for 1 hour, then to 700℃ for 1 hour, then to 1000℃ for 6 hours, and then annealed. The muffle furnace was cooled to room temperature, and finally the CaCu3Ti with an annealing temperature of 1000℃ was obtained. 3.95 Nb 0.15 O 12 Ceramic samples.

[0034] The surface of the prepared sample was ground and polished, the two electrodes of the ceramic piece were coated with conductive silver glue, and the electrical performance was tested after the wires were welded at both ends.

[0035] Example 4 (1) Using deionized water as solvent, calcium nitrate tetrahydrate was fully dissolved, and the mixture was covered with plastic wrap and stirred on a magnetic stirrer for 20 minutes to obtain a colorless and transparent solution A; (2) Take copper nitrate trihydrate and add anhydrous ethanol, cover with plastic wrap and stir on a magnetic stirrer for 40 minutes to obtain a blue transparent solution B. (3) Add tetrabutyl titanate solution to anhydrous ethanol, cover with plastic wrap, and stir in a magnetic stirrer for 20 minutes to form a colorless or light yellow solution C; (4) Using deionized water as solvent, C 10 H5B 20 After fully dissolving, cover with plastic wrap and stir on a magnetic stirrer for 40 minutes to obtain a colorless and transparent solution D; (5) Pour solution A into the continuously stirred solution C, wash beaker A three times with glacial acetic acid, and pour all the washing solution into beaker C. Then carefully and slowly pour solution B into the mixture of A + C. Similarly, wash it three times with glacial acetic acid and pour it into the mixture of A + C to obtain a mixed solution of A + B + C solutions. Then add solution D to the mixed solution of A + B + C. Wash the beaker of solution D three times with glacial acetic acid and pour it into the mixed solution of A + B + C to obtain a mixed solution of A + B + C + D.

[0036] (6) Add a small amount of 65% concentrated nitric acid to the mixed solution of A+B+C+D obtained in (5) to adjust the pH of the solution to 2-3, and cover with plastic wrap to prevent the solution from volatilizing. After magnetic stirring for 2 hours, a light blue CCTO precursor solution is obtained and aged at room temperature for 72 hours to obtain a light blue jelly-like CCTO colloid; (7) The light blue jelly-like CCTO colloid was placed in a vacuum oven at 80°C and dried for 96 hours to obtain a blue-green dry gel, which was then placed in a ball mill and ground into a blue-green powder. (8) The blue-green powder after ball milling was placed in a corundum crucible that had been washed with anhydrous ethanol and dried, and sintered at high temperature in a muffle furnace. The temperature was increased from room temperature to 350°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, then increased to 900°C, kept at this temperature for 10 hours, and cooled to room temperature to obtain a brown powder sample.

[0037] (9) The powder sample obtained in (8) was uniformly mixed with a small amount of 5% PVA adhesive and tableted using a tablet press at a pressure of 10 MPa to obtain dark brown, smooth-surfaced discs.

[0038] (10) The muffle furnace program was set to keep the temperature at 300 °C for 1 hour, then to 700 °C for 1 hour, and then to 900 °C for 6 hours for annealing. The muffle furnace was cooled to room temperature, and finally CaCu3Ti with an annealing temperature of 900 °C was obtained. 3.95 Nb 0.2 O 12Ceramic sample; the muffle furnace program was set to 300℃ for 1 hour, then to 700℃ for 1 hour, then to 1000℃ for 6 hours, and then annealed. The muffle furnace was cooled to room temperature, and finally the CaCu3Ti with an annealing temperature of 1000℃ was obtained. 3.95 Nb 0.2 O 12 Ceramic samples.

[0039] The surface of the prepared sample was ground and polished, the two electrodes of the ceramic piece were coated with conductive silver glue, and the electrical performance was tested after the wires were welded at both ends.

[0040] Figure 1 The XRD diagram of the ceramic sample obtained in Example 1-4 with an annealing temperature of 900°C. It can be seen from the figure that the samples with different doping amounts have strong peaks at the (220), (400), and (422) crystal planes corresponding to the strong peaks of the CCTO standard card, and the characteristic peaks of different doping amounts are shifted compared to the standard spectrum. Figure 2 This is a SEM image of the ceramic sample obtained in Example 1-4 with an annealing temperature of 900°C; it can be seen from the image that the prepared material is composed of particles of several hundred nanometers, with a smooth surface and clear grain boundaries. As the doping amount increases, the grains gradually become smaller.

[0041] Figure 3 The dielectric constant of the ceramic samples of Examples 1-4 changes with frequency. It can be seen from the figure that the dielectric constant decreases with the increase of frequency. With the increase of doping amount, the dielectric constant first decreases, then increases, and then decreases again, all showing giant dielectric properties.

[0042] Figure 4 The graph is a graph showing the variation of the doping amount of the ceramic samples of Examples 1-4 with temperature; it can be seen from the graph that, except for the material with a doping amount of 0.20, the dielectric constants of the other doping materials increase with the increase of calcination temperature.

[0043] Figure 5 The dielectric loss curves of the ceramic samples of Examples 1-4 vary with frequency. The dielectric loss of all doping materials decreases first and then increases with increasing frequency, forming a U-shape.

[0044] Figure 6 The graphs are of the dielectric loss of the ceramic samples of Examples 1-4 as a function of temperature; except for the case where the dielectric loss slightly increases with increasing calcination temperature at 1 MHz when the doping amount is 0.05, the others all show that the dielectric loss decreases with increasing calcination temperature.

[0045] Figure 7 The leakage current variation diagram of the ceramic samples of Examples 1-4; the leakage current at a calcination temperature of 1000°C is generally smaller than that below 900°C.

[0046] Figure 8 The capacitance density of the ceramic samples of Examples 1-4 varies with temperature. The capacitance density of the material with a doping amount of 0.20 decreases with increasing calcination temperature, both at high and low frequencies. The capacitance density of the other doping amounts increases to varying degrees with increasing calcination temperature.

[0047] Therefore, the present application provides a CCTO dielectric ceramic, which uses a compound containing a highly chemically active component as a precursor. The raw materials are evenly mixed under liquid phase conditions, and hydrolysis and condensation chemical reactions are carried out to form a stable transparent sol system, which is not affected by the solid-phase reaction mechanism so that ions are doped into the CCTO lattice at a lower sintering temperature, thereby changing the CCTO microstructure to improve its dielectric properties, and improving the dielectric constant of the material by adjusting the ion polarization rate and lattice distortion, and changing the grain size to increase the interface density and reduce the dielectric loss.

[0048] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.

[0049] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A dielectric CCTO ceramic, characterized in that: The chemical formula of CCTO ceramic is CaCu3Ti 4-x Nb x O 12, Wherein, x>0, the preparation method of the ceramic material is as follows: S1, calcium nitrate tetrahydrate and deionized water were mixed and stirred to prepare solution A; copper nitrate trihydrate and anhydrous ethanol were mixed and stirred to prepare solution B; tetrabutyl titanate solution and anhydrous ethanol were mixed to prepare solution C, and C 10 H5B 20 xH2O and deionized water were mixed and stirred to prepare solution D; S2, mixing solution A, solution B, solution C and solution D to obtain a precursor solution; S3, adding 65% concentrated nitric acid to the precursor solution obtained in S2, adjusting the pH to 2-3, covering with plastic wrap, and after magnetic stirring, aging the obtained CCTO precursor solution at room temperature to obtain CCTO colloid; S4, placing the CCTO colloid obtained in S3 in a vacuum oven at 80°C to dry to obtain a dry gel, and then grinding it into powder in a ball mill; S5. The ball-milled powder in S4 is placed in a corundum crucible washed with anhydrous ethanol and dried, and sintered in a muffle furnace to obtain powder E. S6. Mix the powder E obtained in S5 with a 5% PVA adhesive, and press the mixture into tablets using a tablet press to obtain round tablets with smooth surfaces. S7, annealing the wafer obtained in S6 in a muffle furnace to finally obtain CaCu3Ti 4-x Nb x O 12 Ceramic samples.

2. A CCTO dielectric ceramic according to claim 1, characterized in that: In S1, the specific steps of mixing calcium nitrate tetrahydrate with deionized water to prepare solution A are as follows: after dissolving calcium nitrate tetrahydrate with deionized water as a solvent, the mixture is covered with plastic wrap and stirred on a magnetic stirrer for 20 minutes to obtain solution A.

3. The CCTO dielectric ceramic according to claim 1, characterized in that: In S1, the specific steps of mixing copper nitrate trihydrate and anhydrous ethanol to prepare solution B are as follows: after adding copper nitrate trihydrate to anhydrous ethanol, the mixture is covered with plastic wrap and stirred on a magnetic stirrer for 40 minutes to obtain solution B.

4. The CCTO dielectric ceramic according to claim 1, characterized in that: In S1, the specific steps of mixing tetrabutyl titanate and anhydrous ethanol to prepare solution C are as follows: after adding tetrabutyl titanate to anhydrous ethanol, cover with plastic wrap and stir on a magnetic stirrer for 20 minutes to obtain solution C.

5. The CCTO dielectric ceramic according to claim 1, characterized in that: In S1, C 10 H5B 20 The specific steps of mixing xH2O and deionized water to prepare solution D are: 10 H5B 20 After adding deionized water, xH2O was added, the mixture was covered with plastic wrap and stirred on a magnetic stirrer for 40 min to obtain solution D.

6. The CCTO dielectric ceramic according to claim 1, characterized in that: In S5, the powder after ball milling in S4 is placed in a corundum crucible washed with anhydrous ethanol and dried, and sintered in a muffle furnace to obtain powder E. The specific steps are: placing the powder after ball milling in S4 in a corundum crucible washed with anhydrous ethanol and dried, and sintering, heating the temperature from room temperature to 350°C at a heating rate of 5°C / min, keeping the temperature for 3 hours, then heating to 900°C, keeping the temperature for 10 hours, and cooling to room temperature to obtain powder E.

7. The CCTO dielectric ceramic according to claim 1, characterized in that: In S7, the wafer obtained in S6 is annealed in a muffle furnace to obtain CaCu3Ti 4-x Nb x O 12 The specific steps of the ceramic sample are as follows: the muffle furnace program is set to 300℃ for 1 hour, then heated to 700℃ for 1 hour, then heated to 1000℃ for 6 hours for annealing, and the muffle furnace is cooled to room temperature to finally obtain CaCu3Ti 4-x Nb x O 12 Ceramic samples.

Citation Information

Patent Citations

  • Copper calcium titanate-based ceramic material and preparation method thereof

    CN109776089A

Cited By

  • Modified dielectric ceramic material based on niobium-zirconium double metal element doped copper calcium titanate and preparation method of modified dielectric ceramic material

    CN120647366A

  • Modified dielectric ceramic material based on niobium-zirconium bimetallic element doped calcium copper titanate and preparation method thereof

    CN120647366B